Description of Prescribing Practices in Patients with Upper Gastrointestinal Bleeding Receiving Intravenous Proton-Pump Inhibitors: A Multicentre Evaluation. (1st September 2004) - Enns, Robert; Andrews, Christopher N; Fishman, Martin; Hahn, Michael; Atkinson, Kenneth; Kwan, Peter; Levy, Adrian
Abstract : BACKGROUND: Intravenous forms of proton pump inhibitors (IV PPI) are routinely used for patients with acute upper gastrointestinal bleeding, but a significant concern for their inappropriate use has been suggested. PATIENTS and METHODS: All consecutive patients who received IV PPI (pantoprazole) over 20 months in six Canadian hospitals were reviewed. Prescribing practices, endoscopic findings and outcomes were recorded. RESULTS: A total of 854 patients received IV PPI. Over 90% of patients were given IV PPI for treatment of known or suspected active upper gastrointestinal bleeding. Most patients (69%) underwent upper endoscopy, and 58% of these patients had peptic ulcer disease (PUD). The majority of patients who had endoscopy (57%) had IV PPI administered in advance of the procedure. Of the 334 patients who had IV PPI given in advance, 46 (13.8%) were found to have high risk bleeding PUD stigmata at endoscopy. The remaining 288 patients (86.2%) with advance IV PPI had low-risk PUD lesions or non-PUD lesions; IV PPI was continued after endoscopy in 164 (56.9%) of these patients. CONCLUSIONS: IV PPI is often used before endoscopy in suspected upper gastrointestinal bleed and maintained, regardless of endoscopic findings, after the endoscopy in many Canadian centres. Further study is required to support these clinical practices.